All the 110 papers published in IJABE from the first issue of 2013 to date have been indexed by SCI - Yingkuan, Wang (International Journal of Agricultural and Biological Engineering, 2014)
I am delighted to announce the good news that all the papers published in the International Journal of Agricultural and Biological Engineering (IJABE) from the first issue of 2013 have been abstracted and indexed in the five databases of Thomson Reuters: Science Citation Index (SCI) Expanded (also known as SciSearch®), Journal Citation Reports/Science Edition, Current Contents®/(Agriculture, Biology, and Environmental Sciences), Biological Abstracts and BIOSIS Previews. The coverage and indexing service was traced back to seven past issues of IJABE since I was confirmed this July that the IJABE has been selected for complete coverage in Thomson Reuters products and services beginning with Vol.6(1) 2013. I asked my friend with database access to help with the PDF file including details of indexing records of 110 papers in SCI via Web of Science. Those papers have been published in IJABE from the first issue of 2013 to the fourth issue of 2014 (End of August 2014). I would like to congratulate all the authors on the complete coverage of their papers. I have uploaded PDF file including complete indexing records for free downloading. Meanwhile, I thank all the section editors, associate editors, reviewers, editorial board members, editorial staff and readers for their great support. My special thanks go to my friend who does not wish to be named for providing the coverage records and always making me well-informed about the latest coverage and citation of IJABE papers.